Long‐term performance and biocompatibility of a novel bioresorbable scaffold for peripheral arteries: A three‐year pilot study in Yucatan miniswine. Issue 7 (27th February 2020) - Melnick, Gilberto; Ferrone, Marco; Cheng, Yanping; Conditt, Gerard B.; Guérios, Ênio E.; Rousselle, Serge D.; Granada, Juan F.; Kaluza, Grzegorz L.
Abstract: Aims: Peripheral arteries are constantly exposed to deformation (elongation, twisting, shortening, compression) making bioresorbable scaffolds (BRS) a potentially attractive therapeutic alternative to metallic stents. We conducted a long‐term pilot preclinical study of a novel sirolimus‐eluting BRS in peripheral arteries. Methods and results: Fourteen BRS were deployed in iliofemoral arteries of seven healthy Yucatan miniswine and examined with imaging, pharmacokinetic, histopathologic, and polymer degradation techniques at 0, 30, 90, 180 days, 1, 2, and 3.3 years. Angiographic late luminal loss remained unchanged at 30 and 180 days but significantly decreased from 1 to 3.3 years. optical coherence tomography (OCT) showed late increase in lumen area (1 year: 14.70 ± 3.58 mm 2, 2 years 22.04 ± 3.81 mm 2, and 3.3 years 23.45 ± 7.07 mm 2 ; p < .05) primarily due to scaffold area enlargement between 1 and 3.3 years, while there was no difference in the percent area stenosis at all time points. Histologic evidence of scaffold degradation was observed starting at 2 years, with minimal inflammatory reaction. At 3.3 years, BRS struts were rarely discernible by OCT, confirmed by a nearly complete polymer degradation by molecular weight analysis. Conclusions: In this pilot study, novel sirolimus‐eluting BRS showed promising acute and chronic performance in the iliofemoral arteries of Yucatan miniswine.